2011
DOI: 10.1002/em.20644
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of K‐Rascodon 12 mutations in the F344 rat distal colon following azoxymethane exposure

Abstract: Azoxymethane (AOM) administration to F344 male rats is a widely used model of human colon carcinogenesis. The current study investigates quantitatively the accumulation of K-Ras codon 12 mutations following AOM exposure. Male, 6-week-old F344 rats were treated subcutaneously with 30 mg/kg body weight of AOM, and colon tissue was collected at 1, 8, 24, and 32 weeks after treatment. The K-Ras codon 12 GGT to GAT and GGT to GTT mutant fractions (MFs) were measured using allele-specific competitive blocker polymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Evaluation of more than one mutation by ACB-PCR has been used as a paradigm to detect chemical-specific effects on mutation frequency. In the rat colon cancer model, for example, azoxymethane induced Kras codon 12 GAT mutations, but not codon 12 GTT mutations, which was consistent with the mutational specificity expected for azoxymethane [54]. Conversely, Big Blue rats treated with N -hydroxy-2-acetylaminofluorene ( N -OH-AAF) had significantly increased levels of both mutations in liver DNA, even though induction of G to T mutation was the primary mutational specificity observed in the LacI neutral reporter gene of the liver DNA from the same rats.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Evaluation of more than one mutation by ACB-PCR has been used as a paradigm to detect chemical-specific effects on mutation frequency. In the rat colon cancer model, for example, azoxymethane induced Kras codon 12 GAT mutations, but not codon 12 GTT mutations, which was consistent with the mutational specificity expected for azoxymethane [54]. Conversely, Big Blue rats treated with N -hydroxy-2-acetylaminofluorene ( N -OH-AAF) had significantly increased levels of both mutations in liver DNA, even though induction of G to T mutation was the primary mutational specificity observed in the LacI neutral reporter gene of the liver DNA from the same rats.…”
Section: Discussionmentioning
confidence: 52%
“…Comparisons of KRAS codon 12 GAT (G12D) and GTT (G12V) MF in a variety of human and rodent tissues has demonstrated that the KRAS codon 12 GAT mutation is generally the more abundant spontaneous mutation, often present in normal human or control rodent tissues at frequencies up to ten-fold greater than the KRAS codon 12 GTT (G12V) mutation [37, 38, 54, 55]. In contrast, we observed significantly higher levels of GTT mutations than GAT mutations in the mouse ovary in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…In the ACB-PCR studies described above, as well as other studies [McKinzie et al, 2006;McKinzie et al, 2007], it has been possible to measure the induction of oncomutations at relatively short times after in vivo carcinogen exposure. Additional studies with a variety of chemicals will be needed to establish whether and how carcinogen effect can be monitored using such methods as part of 28-or 90-day repeat dose toxicity testing.…”
Section: Sensitivity and Dose-response Assessmentmentioning
confidence: 98%
“…Allele-specific competitive blocker PCR (ACB-PCR) is a DNA-based mutation detection method that can quantify specific base pair substitutions present in DNA samples with allele frequencies as low as 1 mutant per 100,000 wild-type sequences [37,38,4244]. Unlike approaches for mutation detection that report the presence or absence of mutation, the output of ACB-PCR is a measured mutant fraction (MF), which is the ratio of mutant allele to wild-type allele within a given DNA sample.…”
mentioning
confidence: 99%